Body work : beauty and self-image in American culture - Gimlin, Debra L., 1967- (University of California Press, 2001)
"Beautifully written, cleverly argued, and skillfully researched, Debra Gimlin's Body Work goes beyond the argument that the beauty industry exists only to control women. Instead, Gimlin examines women's relationship to beauty from a feminist sociological perspective, finding that women are not dupes of the beauty industry but rather use body work in both empowering and degrading ways. It's about time a sociologist delved into women's complicated relationship to the beauty industry!"--Verta Taylor, author of Rock-a-By Baby: Feminism, Self-Help, and Postpartum Depression"This fascinating study r